Manipulation behavior and therapeutic relationship - Fukuda, Ilza Marlene Kuae (1982)
The authors present a bibliographical review about concept and modalities of manipulative behavior and consider the importance of such manipulation in the therapeutic nurse-patient relationship. They emphasize the importance of the nurse being aware of about the occurence of this behavior, list some patient's manifestations and comment them, giving especial attention to the therapeutic measures to be taken.